Pengembangan Formula Enteral Rendah Lemak Berbasis Pangan Lokal (Labu Kuning dan Tepung Kedelai) sebagai Strategi Peningkatan Kualitas Pelayanan Gizi Rumah Sakit - Munitya Anjalya Pertiwi; Rani Nurmayanti (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Low-fat enteral nutrition is an essential component of hospital nutritional support for patients with fat intolerance, hepatobiliary and pancreatic disorders, and post operative conditions. Nevertheless, standard hospital formulas frequently present limitations in nutritional adequacy, physical properties particularly texture and sensory acceptability. This study aimed to evaluate the effects of varying concentrations of pumpkin flour and soybean flour on the nutritional composition, viscosity, flow rate, and sensory acceptability of a low-fat enteral nutrition formula. A quasi experimental study employing a post-test-only control group design was conducted by comparing a standard hospital formula (F0) with two modified formulations (F1 and F2). The study was performed from October to December 2025 at RSUD Gambiran Kediri and the Integrated Laboratory of Poltekkes Kemenkes Malang. Hedonic testing involved 20 nutrition students using a 4-point hedonic scale. Nutritional composition was calculated based on the Indonesian Food Composition Table. Sensory data were analyzed using the Kruskal Wallis and Mann Whitney U tests, while flow rate was assessed using one-way ANOVA. The findings indicated that the modified formulations significantly increased energy and protein content compared with the standard formula while maintaining low fat levels. Formula F2 exhibited the most favorable physical characteristics, with a flow rate of 5.14 cc/s and a viscosity of 427.5 cP, and achieved the highest acceptance scores for taste and color (p < 0.05). All formulations complied with hospital food service budget standards. Therefore, F2 demonstrates strong potential as a nutritionally adequate and acceptable alternative low-fat enteral formula.